Ethical Issues In Medical Tourism In Africa - Olojede, Helen Titilola (African Journal of Stability and Development (AJSD), 2025)
Medical tourism, (MT) the act of moving from one country to another to seek medical assistance, is a global phenomenon. Despite being an international occurrence with lots of literature on its social, political, or economic implications, this paper articulates its ethical concerns to the patient or ‘tourist’, the host and the destination countries. It, thus, addresses questions such as: what are some ethical issues in medical tourism? Is medical tourism a leisure enterprise, as the name suggests? Are there justifications for medical tourism? Adopting the scoping review methodology, the paper explores and synthesises existing literature to foreground a critical analysis of the ethical implications of medical tourism. Some of its findings concern ethical issues such as harm/risks, inequity/inequality of healthcare distribution, informed consent, and duty of care/quality of care. In addressing these issues, while critically analysing the adequacy of deontological ethics and preference utilitarianism, the paper argues that it is imperative that Africa not just compete for the global MT dollar but sit up and regulate MT activities. This requires coming up with a framework that would strike a balance between the benefits of MT and the burden of it. To this end, this paper proposes a regulation that promotes the common good of all: the patient, the departure and destination countries.